Red lines in nuclear nonproliferation. Issue 3 (4th May 2017) - Altman, Dan; Miller, Nicholas L.
ABSTRACT: States that seek to prevent nuclear proliferation through threats of force or sanctions often set "red lines, " which set limits on nuclear capabilities beyond which a proliferator must risk triggering a punitive response. Yet despite a wide range of possible red lines that states could choose—for example, constructing a nuclear weapon (weaponization), enriching uranium, or conducting a nuclear test—the academic literature is nearly silent on the tradeoffs inherent in selecting one of these red lines over another. Specifically, what are the vulnerabilities in each red line that proliferators can exploit to advance their nuclear program while limiting the punitive response? To address this question, this article introduces a theory of red lines and how they are challenged. We apply this theory to red lines in nuclear nonproliferation and offer historical evidence to support it.